2011
DOI: 10.1002/ajh.22229
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of weekly intravenous immunoglobulin prophylaxis versus intravenous immunoglobulin by IgG level monitoring in hematopoietic stem cell transplant recipients

Abstract: Patients undergoing allogeneic hematopoietic stem cell transplant (allo HCT) have a higher incidence of infections partly due to secondary hypogammaglobulinemia. We evaluated the role of IVIG in allo HCT patients who received prophylactic IVIG 200 mg/kg once weekly regardless of IgG level (Group 1, n 5 115) compared with patients who received IVIG based on IgG level <400 mg/dL (Group 2, n 5 114). Primary endpoints were the utilization of IVIG, incidence of veno-occlusive disease (VOD), graft-versus-host diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In another recent study by Howell et al, they compared the allogeneic adult HSCT patients receiving prophylactic IVIG once weekly regardless of IgG level versus the patients receiving IVIG based on IgG level <400 mg/dL. In their study, they reported that there were no significant differences between the two groups and recommended monthly monitoring of IgG level and replacement only if IgG level is <400 mg/dL (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another recent study by Howell et al, they compared the allogeneic adult HSCT patients receiving prophylactic IVIG once weekly regardless of IgG level versus the patients receiving IVIG based on IgG level <400 mg/dL. In their study, they reported that there were no significant differences between the two groups and recommended monthly monitoring of IgG level and replacement only if IgG level is <400 mg/dL (29).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, there were no significant differences between the use of IVIG and Pentaglobin Ò regarding the incidence of all grades of GVHD, VOD, or infections including bacteremia, septicemia, local infection, CMV reactivation, and CMV disease. On the basis of the Centers for Disease Control recommendations in 2000 and the results of the recent studies and meta-analysis, current recommendation is not to administer IVIG as prophylaxis within the first 100 days after allo-HSCT, except high-risk allogeneic HSCT recipients with severe hypogammaglobulinemia (i.e., IgG < 400 mg/dL) (28,29,35,36). The present study's results also support current recommendations, even though lack of a placebo control group.…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8][9][10][11] In a randomized prospective trial of 382 patients (30% were o20 years of age), the patients received 500 mg/kg weekly IVIG infusions until day 90 and then monthly until 1 year were compared with the control group. 10 The control group had a significantly higher risk of Gramnegative systemic infections, as well as local infections.…”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective study, the outcome of 115 patients who received IVIG infusions weekly for 3 months post transplant were compared with 114 patients who received IVIG if the IgG level was o400 mg/dL. 8 There was no difference in the incidence of acute GVHD, TRM and infections between the two groups. In a large controlled trial of monthly IVIG prophylaxis between day 90 and 365 post transplant, the authors observed a higher rate of localized infection in the control group but no effect on mortality related to chronic GVHD or OS.…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies in adults have shown that level-based dosing does not impact infection rates. 1,7,8 One pediatric study showed that at 1-year post-HSCT the cumulative incidence of CMV was higher in patients in patients who did not receive monthly IVIG. 9 Our study is the first to analyze IVIG dosing by levels in the pediatric HSCT population and the effect on multiple types of infections.…”
Section: Discussionmentioning
confidence: 99%